Teaching gender issues with chick flicks in FTKW, UMK - Iwan Zahar (2012)
The use of questionnaries and interviews, student’s porfolio, and academic transcript are not sufficient to know background of students and their previous knowledges. The objective of the research is to use of movies as supporting criteria to know student’s prior knowledge, and also other useful information to improve student’s performance, and other useful information such as communication skills, high order thinking and valuing. The survey method was undertaken in 20 third year product design students and 9 fourth year multimedia students, Universiti Malaysia Kelantan, Malaysia.